Utilization of Coffee Husk and Bagasse Waste as Biobriquettes - Yasir Amani Yasir Amani; Muhammad Sayuthi; Dede Irawan; Faisal Muhammad Nur; Heindrix Hidayat (Journal of Mechafa Engineering and Fabrication, 2026)
Utilising agricultural waste as an alternative energy source is an effort to reduce dependence on fossil fuels and its negative impact on the environment. This research aims to examine the characteristics of biobriquettes from a mixture of coffee husk waste and sugarcane bagasse using sodium silicate adhesive, as well as analyse the effect of variations in material composition on the physical and thermal properties of biobriquettes. The composition of the ingredients varied in five ratios of coffee skins and sugarcane bagasse (80:20, 70:30, 50:50, 30:70, and 20:80) grams with 15% sodium silicate adhesive. The proximate test results showed that the highest water content was 4.336%, the highest ash content was 0.69%, the highest volatile matter was 87.218%, and the highest bound carbon was 17.946%. For the test results, the highest calorific value was 6231.715 cal/gram with a composition of 80 coffee skins and 20 grams of sugarcane bagasse. This research proves that a mixture of coffee skins and sugar bagasse with sodium silicate adhesive has great potential as an alternative fuel, with the dominance of coffee skins producing more optimal biobriquette characteristics